Tutupan Terumbu Karang pada Kedalaman Berbeda di Perairan Pantai Batu Sungu, Desa Les, Kabupaten Buleleng - I Putu Dede Charles Dharma Saputra; IGB Sila Dharma; Yulianto Suteja; Widiastuti Widiastuti (Department of Marine Sciences, Faculty of Marine Science and Fisheries, Udayana University, 2021)
Bali island has many magnificent underwater coral reef gardens that attract tourists. Besides Pemuteran and Menjangan island waters, Batu Sungu water has also potential to be a new tourist destination. Thus, to determine the potency and management plan in Batu Sungu waters, this research aimed to examine the overall coral cover, coral growth forms, other benthic forms, and each of their components in 5 and 10 m depths. The overall coral cover, coral growth forms, other benthic forms, and each of their components were counted by using the Line Intercept Transect (LIT) method. Before collecting data, study sites were observed by using the Manta Tow method. Data were collected in 2 depths (5 dan 10 m) with 5 sites each (replicates) that separates within 50 to 150 m. A 25 m LIT was spread parallel to the coastline above the reefs. Live coral colonies, other benthic forms below the transects were measured for the number, length, and growth forms. Water quality was measured in situ (temperature, current, and clarity) and ex situ (pH). Results showed that the category of coral coverage in Batu Sungu water is